Migration in Bronze Age southern China: multidisciplinary investigations of elite Chu burials in Jingzhou. (April 2022) - Xu, Yiran; Sheng, Pengfei; Xiong, Jianxue; Meng, Hailiang; Wei, Pianpian; Sun, Chang; Jia, Hanqing; Liu, Jianye; Tian, Yong; Sun, Fan; Wen, Shaoqing
Abstract: Abstract : Reconstructing the history of elite communication in ancient China benefits from additional archaeological evidence. We combine textual analysis with new human stable carbon and nitrogen isotope data from two Chu burials in the Jingzhou area to reveal significant dietary differences among Chu nobles of the middle Warring States period ( c . 350 BC). This research provides important new information on the close interaction between the aristocratic families of the Qin and Chu.